Knee Stability following Posterior-Stabilized Total Knee Arthroplasty: Comparison of Medial Preserving Gap Technique and Measured Resection Technique - Tsubosaka, Masanori; Muratsu, Hirotsugu; Nakano, Naoki; Kamenaga, Tomoyuki; Kuroda, Yuichi; Inokuchi, Takao; Miya, Hidetoshi; Kuroda, Ryosuke; Matsumoto, Tomoyuki (The Journal of Knee Surgery, 2021)
Novel medial preserving gap technique (MPGT) focuses on medial compartment stability and allows lateral physiological laxity. This study aimed to compare the MPGT with the measured resection technique (MRT) to determine which provides better postoperative knee stability after posterior-stabilized total knee arthroplasty (PS-TKA). Primary PS-TKA, using either MPGT (n = 65) or MRT (n = 65), was performed in 130 patients with varus knee osteoarthritis. Postoperative knee stabilities at extension and flexion were assessed using varus–valgus stress radiographs and stress epicondylar view, respectively (at 1 month, 6 months, 1 year, and 3 years postoperatively). The distance between the femoral prosthesis and polyethylene insert was measured on each medial and lateral side, defined as the medial joint opening (MJO) and lateral joint opening (LJO), respectively. Decreasing MJO or LJO translated to increasing postoperative stability. The femoral external rotation angle was compared between the two surgical techniques; postoperative knee stability was also compared between the medial and lateral compartments, as well as the surgical techniques. A significant difference was found in the femoral external rotation angle between MPGT (4.2 ± 0.2 degrees) and MRT (3.6 ± 0.1 degrees, p < 0.01). Postoperative MJOs both at extension and flexion were significantly smaller than LJOs using MPGT and MRT at all time points (p < 0.05). MJOs and LJOs at extension using MPGT were significantly smaller than those when using MRT, at 1 and 3 years postoperatively (p < 0.05). Furthermore, MJOs at flexion using MPGT were significantly smaller than those when using MRT at 6 months, 1 year, and 3 years postoperatively (p < 0.05). MPGT provided higher postoperative medial knee stability than MRT both at extension and flexion, even at 3 years after PS-TKA. This suggests that this newly developed surgical technique is a more feasible option than MRT for the preservation of postoperative medial knee stability.
Keywords: total knee arthroplasty; postoperative knee stability; posterior-stabilized; medial preserving gap technique; measured resection technique; soft tissue balance